Coaching matters - Dick, F. (New Studies in Athletics, 2015)
In a rapidly changing world, one in which the paradigm of coaching and coaching relationships has shifted significantly, the coaches themselves do not seem to have kept up. The greater role of sport science, technology and performance related services in the coaching process have all transformed the climate of support for both performer and coach alike. The author, a former national head coach in athletics, argues that coaches, who in general worked to achieve many of the changes that have taken place in the last 30 years were not, in fact, prepared for the consequences - nor was the culture of athletics. After outlining the various consequences and pointing out that failure to address them will lead to an erosion of what coaching is and who coaches are, he proposes actions under four headings: Education, Regulation, Representation and Leadership. These include a review of coach education programmes, a body to regulate the craft of coaching, a coaches' charter and a greater role for coaches associations. He concludes that in the end it will come down to coaches committing to make it happen and delivering on that commitment.